Landscape and public politics in Mexico. A relationship to be resolved (REVISTA NODO, 2019)
The landscape has been forgotten about in the environmental and territorial politics of Mexico. Furthermore, it has a very insufficient consideration in the legal framework. Despite this, civil society and universities are doing a remarkable job to reverse this poor consideration of the landscape as a territorial and environmental management tool and promoting its correct implementation in Mexican public politics.
Keywords: Mexico; Landscape; Public politic; University; Laws